2020
DOI: 10.32794/mr11250054
|View full text |Cite
|
Sign up to set email alerts
|

Plant Perception of Light: The role of indoleamines in Scutellaria species

Abstract: Light mediates plant growth through diverse mechanisms and signaling networks including plant growth regulators (PGRs). We hypothesized that a novel class of PGRs, the indoleamines, are plant signaling molecules that perceive changes in light composition and initiate a cascade of metabolic responses. We used three Scutellaria model species (skullcap): S. lateriflora, S. galericulata and S. racemosa that produce high levels of melatonin and serotonin to investigate this hypothesis. Axenic Scutellaria cultures w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…Exposure to red light leads to immediate accumulation of Ser in Scutellaria, which decreases over 7 days. In contrast, Mel is detected in plants grown under blue light [60]. Using a short-day flowering plant, Chenopodium rubrum, Kolářet al [61] showed that light suppresses Mel biosynthesis in plants.…”
Section: Discussionmentioning
confidence: 99%
“…Exposure to red light leads to immediate accumulation of Ser in Scutellaria, which decreases over 7 days. In contrast, Mel is detected in plants grown under blue light [60]. Using a short-day flowering plant, Chenopodium rubrum, Kolářet al [61] showed that light suppresses Mel biosynthesis in plants.…”
Section: Discussionmentioning
confidence: 99%
“…In one of the study it was reported that 3 months of red light exposure led to increased melatonin levels in Glycyrrhiza uralensis (licorice) plants than those grown under blue or white light (Afreen et al, 2006). A similar effect was found in Scutellaria racemosa where short time exposure to blue light initially led to increased melatonin levels but long term red exposure resulted in increased endogenous melatonin concentrations (Forsyth et al, 2020). Overall, there is a strong relationship between light and melatonin whose mechanism has yet to be described thoroughly (Forsyth, In one of the study, relation between the different melatonin content of two cultivars of Nicotiana tabacum and its susceptibility to ozone has been suggested (Dubbels et al, 1995;Hattori et al, 1995).…”
Section: Influence Of Dietary Sources Of Melatonin On Sleep Qualitymentioning
confidence: 79%
“…Moreover, Ser showed strong antioxidant effect but less influence on ABA related gene upregulation. Both Mel and Ser can act as antioxidants, exhibit wide ranging effects in plant development under normal and stress conditions, and are known to improve survival of plants in response to biotic and abiotic stresses (21,(59)(60)(61)(62)(63). In addition to antioxidation, these stress survival mechanisms may include altered biosynthesis, redistribution, interconversions and feedback mechanisms in the indoleamines pathway (23).…”
Section: Discussionmentioning
confidence: 99%